عبداللہ حسین کے ناولوں میں مذہب تصوف اور سیاست کے معنیاتی پیراڈائمMeaningful Paradigm of Religion, Tasawwuf and Politics in the Novels of Abdullah Hussain (Al-Qamar, 2023)
With his efforts of half a century, Abdullah Hussain has put history in front of his fellow Nasr generation and future generations with his dream consciousness and waking life.  By removing many layers layer by layer, he exposed it in front of us as if it was in my heart too, highlighted all aspects of life and presented his stories in the form of art.  He will always live because of his unique style, Urdu manners and light have been given to him that till today his art and thought are criticized by critics from different dimensions. He is a creator as well as a historian and a researcher. And have a thorough understanding of the basic teachings of their service.
Keywords: History; Different Dimensions; Creator; Highlighted; New Generation; Basic Teaching; Fellow; Exposed